Respuesta :

Answer:

A

Step-by-step explanation:

Given the 2 equations

4x + 5y = - 12 → (1)

- 2x + 3y = - 16 → (2)

Eliminate the x- term by multiplying (2) by 2 and adding the result to (1)

- 4x + 6y = - 32 → (3)

Add (1) and (3) term by term

11y = - 44 ( divide both sides by 11 )

y = - 4

Answer:

A.  -4

Step-by-step explanation:

To find the y-value in the solution to this system of linear equation, we will follow the steps below:

4x + 5y = −12  ------------------------------------------------------(1)

-2x + 3y = −16 -----------------------------------------------------(2)

Multiply through equation (1)   by  2   and multiply through equation (2) by 4  to make the x coefficient have equal value

8x + 10y = -24 ---------------------------------------------------(3)

-8x + 12y = -64 ---------------------------------------------------(4)

Add equation (1) and equation (2)

22y = -88

Divide both-side of the equation by 22

22y/ 22 = -88/ 22

y =-4